Gender variation of Dryas octopetala along snowmelt and latitudinal gradients in the Subarctic and the High Arctic - Wada,Naoya; Kudo,Gaku; Kojima,Satoru (National Institute of Polar Research, 1999)
P(論文) We describe variations of floral traits of Dryas octopetala L. along a snowmelt gradient within and among three sites : 1) the Subarctic Latnjajaure in northernmost Sweden, 2) the High Arctic Longyearbyen and 3) Ny-Alesund, Svalbard in Norway, also High Arctic. Dryas octopetala had two types of flowers, hermaphrodite flowers and male flowers, lacking any gynoecium. The frequency of male flowers was higher in late snow-melt habitats (i. e. late flowering populations) both at Latnjajaure and Ny-Alesund. Male flowers were significantly lighter in dry weight than hermaphrodite flowers; the difference was larger in the High Arctic than in the Subarctic, suggesting a higher resource limitation in male flowers in the High Arctic. Flower weight also varied among the three sites, and showed a significant difference along the latitudinal gradient both in hermaphrodite and male flowers. In the hermaphrodite flowers, the gynoecium dry weight differed among the three sites, being significantly heavier at Latnjajaure than at Longyearbyen and Ny-Alesund. As a result, the "femaleness" (gynoecium weight/androecium+gynoecium weight) showed significantly higher values at Latnjajaure than at Longyearbyen and Ny-Alesund. Thus, the floral allocation to female function in D. octopetala decreases with an increase in latitude from the Subarctic to the High Arctic. Gender variation of flowers is a size-dependent phenomenon; a positive correlation between flower size and femaleness was observed within each site. departmental bulletin paper